Interpersonal skills in organizations - De Janasz, Suzanne C.; Dowd, Karen O.; Schneider, Beth Z. (McGraw Hill, 2022)
"The emphasis in this edition focuses on making the text more current and enhancing its pedagogic effectiveness for students and instructors"--